Comparison of the Post Treatment Outcomes of a Conservative Physiotherapy Protocol for Subacromial Impingement Syndrome in Terms of Acromion Morphology - Turhan, Begümhan; Doğan, Hilal; Maden, Çağtay (European Journal of Therapeutics, 2024)
Objective: The present study aimed to compare the results of a conservative physiotherapy (CP) protocol for subacromial impingement syndrome (SIS) in terms of the morphological types of acromion. Methods: Fifty patients participated in the present study, and they were divided into 3 groups according to the acromion morphology types. A 8-week CP (4-week treatment period at the clinic and, in addition, an exercise program at home for 4 weeks) was applied to all patients. The patients were evaluated in terms of pain (at rest and activity) by the Visual Analog Scale, range of motion (ROM), joint position sense (laser pointer), muscle strength (digital dinamometer), and functionality (the Shoulder Pain and Disability Index, SPADI) before and after the treatment. Result: In the pre- and post-treatment changes (delta), the shoulder flexion angle increased less in the type 3 group than in the type 1 and type 2 groups (p<0.05). In the shoulder abduction angle, there was a similar increase in the type 3 group compared to the type 2 group, while there was less increase in the type 1 group (p<0.05). It was determined that there was more deviation in the change value of shoulder abduction position sense in the type 3 group compared to the other groups (p<0.05). There was no difference between the groups in the change values of pain, muscle strength, or the SPADI score (p > 0.05). Conclusion: Type 3 acromion may have a handicap in improving shoulder flexion and abduction ROM and shoulder abduction position compared to other types.